Sistem Pendukung Keputusan (SPK) Pemilihan Tanaman Pangan Berdasarkan Kondisi Tanah Menggunakan Metode ELECTRE dan TOPSIS - Ningsih Puji Rahayu; Rekyan Regasari Mardi Putri; Agus Wahyu Widodo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Indonesia is a country with a very strategic geographical location, it is very beneficial for citizens because almost all plants can be planted in Indonesia. Especially the food crop. Food crops are plants that are very important for the role of living creatures, especially humans. Among the food crops are rice, corn, peanuts, soybeans, these four plants have a very important role for national food security. In every region in Indonesia have different types of soil and certainly the fit for different crops as well. From four food crops namely rice, corn, peanuts and soybeans. (Cm), peat thickness (cm), ph h2o, salinity (dS / m), alkalinity% of the soil,, Depth of sulfidation (cm), slope (%). Of the 12 criteria that will be matched with existing soil conditions klaten. By matching the suitability of the land based on these criteria it will be easier for farmers in determining what food crops are suitable for the area so then the agricultural output will be increased. ELECTRE and TOPSIS method is a multicriteria decision-making analysis method, ELECTRE is based on the concept of outrangking by using pairwise comparison of alternatives based on each appropriate criteria. In this study why use the ELECTRE method because the electre method is very suitable for use in cases that have many criteria and alternatives. The accuracy is 85.714% using 28 data.